(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2022)
The objectives of the research focus on defining the sources of deriving the childs culture and social upbringing with the intention of determining the characteristics of the childs culture determining the main foctors in the type of child socialization,and clarifying the most important foctors that help in changing the culture of society on children and contemporary challenges using digitalscientific communication sites with an explanation of the childs psychological growth in eriksons theory and its impact on child cuilure .and clarify the reasons that prevent the child and culture with a focus on the contemporary challenges of the childs culture . The research delegation came out with a number of conclusions which were . The most important climatesand the most influential on academic achievement is the family community climate ,so that the level of family culture , its capabilities and its ability to help the child in his academic achievement , as well as the availability the family climate predisposing to achievement and based on positive interactions between the child ,his parents and his siblings , as well as the care and positive familial orientation of the children are all conditions and factors whose exisitence leads to the achievement of Encouraging children to use digital scientific communication sites, which is the most important challenge facing educationl instituttions in developing countries , which confirms the need to employ e- learning and e- teaching to develop the educational performance of the child if the studies confirm that modem technology is not necessarily the cure for all problems . In light of the conclusions that the research came out with, we recommend the following . 1-taking into account the similarities and differences between children ,developing their comparative skills , classification and dialogue , and the importance of following up on their use of digital scientific communication sites . 2-summarizing and taking notes , summarizing the main ideas that focus on analyzing informationand thus enhancing childrens , understanding of the curriculum content using the most important modem technologies